38 of the bags have zips but no buttons
Answer:
5.2 ft.
Step-by-step explanation:
First you want to find the circumference of the circle. Given the radius 5ft you can then multiply it by 2 to get the diameter to make the equation for circumference much easier. 2*5=10. the diameter is 10ft.
Next the formula for circumference with diameter is π(d). Our diameter is 10 so plug it in and you get π(10) which equals about 31.4.
With the 60 degree you have to know that a circle is a full 360 degrees. 60 is 1/6 of 360 in meaning the distance the weight at the end of the cord will move is 1/6 of the circumference of this circle. Therefore you need to do 1/6*31.4 which equals about 5.2.
Answer:
a = 4,
b = 12
c = 10
d = 15
Step-by-step explanation:
Since the product of each column is equal, therefore,
b*5 = 60
b = 60 ÷ 5 = 12
c*6 = 60
c = 60 ÷ 6 = 10
Since the sum of each column are equal, therefore,
12 + 10 + a = 5 + 6 + d
22 + a = 11 + d
Think of a number you can add to 22, and another number you can add to 11, which will make both sides equal. Add both numbers, whenmultiplied together should give you 60.
Factors of 60 are:
(a, d)
(1, 60) => 22 + a = 11 + d => 22+1 = 11+60 (incorrect)
(2, 30) => 22 + a = 11 + d => 22+2 = 11+30 (incorrect)
(3, 20) => 22 + a = 11 + d => 22+3 = 21+20 (incorrect)
(4, 15) => 22 + a = 11 + d => 22+4 = 11+15 => 26 = 26 [CORRECT]
(5, 12) => 22 + a = 11 + d => 22+5 = 11+12 (incorrect)
(6, 10) => 22 + a = 11 + d => 22+6 = 11+10 (incorrect)
Therefore,
a = 4,
d = 15
Answer:
The solution is ![x =0.](https://tex.z-dn.net/?f=x%20%3D0.)
Step-by-step explanation:
The equation
![\bold{(1).}\: sin(\dfrac{3\pi }{2} +x)+sin(\dfrac{3\pi }{2} +x) =-2](https://tex.z-dn.net/?f=%5Cbold%7B%281%29.%7D%5C%3A%20sin%28%5Cdfrac%7B3%5Cpi%20%7D%7B2%7D%20%2Bx%29%2Bsin%28%5Cdfrac%7B3%5Cpi%20%7D%7B2%7D%20%2Bx%29%20%3D-2)
can be rewritten as
![2* sin(\dfrac{3\pi }{2} +2) =-2](https://tex.z-dn.net/?f=2%2A%20sin%28%5Cdfrac%7B3%5Cpi%20%7D%7B2%7D%20%2B2%29%20%3D-2)
and can be further simplified to
.
Now, taking the inverse sine of both sides we get:
![sin^{-1}(sin(\dfrac{3\pi }{2} +x) =sin^{-1}(-1)](https://tex.z-dn.net/?f=sin%5E%7B-1%7D%28sin%28%5Cdfrac%7B3%5Cpi%20%7D%7B2%7D%20%2Bx%29%20%3Dsin%5E%7B-1%7D%28-1%29)
![\bold{(2).}\: \dfrac{3\pi }{2} +2 =sin^{-1}(-1)](https://tex.z-dn.net/?f=%5Cbold%7B%282%29.%7D%5C%3A%20%20%5Cdfrac%7B3%5Cpi%20%7D%7B2%7D%20%2B2%20%3Dsin%5E%7B-1%7D%28-1%29)
The value of the right side on the interval
is
,
which makes the equation (2)
![\dfrac{3\pi }{2}+x =\dfrac{3\pi}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7B3%5Cpi%20%7D%7B2%7D%2Bx%20%20%3D%5Cdfrac%7B3%5Cpi%7D%7B2%7D)
solving for
gives
![\boxed{x = 0}](https://tex.z-dn.net/?f=%5Cboxed%7Bx%20%3D%200%7D)
which is our solution.